Comparing biosimilar SB2 with reference infliximab after 54 weeks of a double-blind trial: clinical, structural and safety results - Smolen, Josef S; Choe, Jung-Yoon; Prodanovic, Nenad; Niebrzydowski, Jaroslaw; Staykov, Ivan; Dokoupilova, Eva; Baranauskaite, Asta; Yatsyshyn, Roman; Mekic, Mevludin; Porawska, Wieskawa; Ciferska, Hana; Jedrychowicz-Rosiak, Krystyna; et al. (Rheumatology (Oxford, England), 2017)
OBJECTIVES: SB2 is a biosimilar to the reference infliximab (INF). Similar efficacy, safety and immunogenicity between SB2 and INF up to 30 weeks were previously reported. This report investigates such clinical similarity up to 54 weeks, including structural joint damage. METHODS: In this phase III, double-blind, parallel-group, multicentre study, patients with moderate to severe RA despite MTX were randomized (1:1) to receive 3 mg/kg of either SB2 or INF at 0, 2, 6 and every 8 weeks thereafter. Dose escalation by 1.5 mg/kg up to a maximum dose of 7.5 mg/kg was allowed after week 30. Efficacy, safety and immunogenicity were measured at each visit up to week 54. Radiographic damage evaluated by modified total Sharp score was measured at baseline and week 54. RESULTS: A total of 584 patients were randomized to receive SB2 (n = 291) or INF (n = 293). The rate of radiographic progression was comparable between SB2 and INF (mean modified total Sharp score difference: SB2, 0.38; INF, 0.37) at 1 year. ACR responses, 28-joint DAS, Clinical Disease Activity Index and Simplified Disease Activity Index were comparable between SB2 and INF up to week 54. The incidence of treatment-emergent adverse events and anti-drug antibodies were comparable between treatment groups. Such comparable trends of efficacy, safety and immunogenicity were consistent from baseline up to 54 weeks. The pattern of dose increment was also comparable between SB2 and INF. CONCLUSION: SB2 maintained similar efficacy, safety and immunogenicity with INF up to 54 weeks in patients with moderate to severe RA. Radiographic progression was comparable at 1 year. TRIAL REGISTRATION: ClinicalTrials.gov (http://clinicaltrials.gov; NCT01936181) and EudraCT (https://www.clinicaltrialsregister.eu; 2012-005733-37).
Keywords: rozvrh dávkování léků; dospělí; infliximab; Infliximab; tumour necrosis factor blocker; Biosimilar Pharmaceuticals; Flixabi; monoclonal antibody; Arthritis, Rheumatoid; Female; radiografie; Radiography; revmatoidní artritida; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; Drug-Related Side Effects and Adverse Reactions; lidé; dvojitá slepá metoda; Drug Administration Schedule; Treatment Outcome; radiographic progression; stupeň závažnosti nemoci; biosimilární léčivé přípravky; nežádoucí účinky léčiv; Double-Blind Method; Male; progrese nemoci; Aged; Disease Progression; Antirheumatic Agents; Young Adult; rheumatoid arthritis; Renflexis; Sharp score; lidé středního věku; senioři; mužské pohlaví; Severity of Illness Index; antirevmatika; Remicade; Middle Aged; biosimilar; Humans